Some Anatomical Features in the Respiratory System of Chiloloba orientalis D & R (Coleoptera: Scarabaeidae) - Saraf, Surekha (Recent Research in Science and Technology, 2011)
Chiloloba orientalis D & R is an economically important pest on bajra (Pennisetum typhoides Rich), Jowar (Sorghum vulgare Pers) crops. This study will be the basis for a future comparative examination of the internal anatomy of Scarabaeid beetle. The respiratory system shows a typical tracheo-spiracular system with the air-sacs. The air-sacs are quite distensible and collapsible. The air-sacs are specially pronounced in insects, which are the most active ventilators.